SOSIALISASI DAN EDUKASI KHASIAT DAUN TEH HIJAU (Camelia sinensis L.) DALAM SEDIAAN HAIR TONIC UNTUK PERTUMBUHAN DAN PERAWATAN RAMBUT DI DESA SUDIREJO KECAMATAN NAMORAMBE - Sembiring, Pintata (Jurnal Pengabdian Masyarakat Putri Hijau, 2025)
This activity aims to educate the community in Sudirejo village about the efficacy of using hair tonic from herbal ingredients, namely from green tea leaves. Where green tea leaves have a strong polyphenol antioxidant content that can prevent hair loss, accelerate hair growth, and can maintain hair health nutrition. This activity involves pharmacists, This activity is expected to increase the understanding of the Sudirejo community about the efficacy of green tea leaves for hair health, and in this activity it is expected to provide information and learning to them about how to process and apply green tea leaves to hair so that people can make their own hair tonic preparations with green tea ingredients. The methods used include presentations, pre-tests and post-tests, interactive discussions, and distribution of educational materials. The results of observations showed an increase in participant awareness of the efficacy of green tea leaves after socialization. This study is expected to encourage hair health patterns